(3Gdfbd HGdeaghejI aj Md CdaGX GdBLQhejIs - (3CHhYHO Gddg TeS GdOjf eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdCfOdSj GdeYQha HGdQGYjs; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s ((3GdYQHj Hf CMeO Hf eMeO Hf YHOGdeDef GdOGhOj GdTQja s)
(3ChdgG (B:s
(3CeG HYO HYV GdaVdGA hGdCUMGH hGdENhGf GdWdHI Ydi Md CdaGX (B"(3GdLQhejI(B" s
(3BNQgG (B:s
(3hGdLhGH gPG Ydi ePgH Gdchajjf GdVejQ jYhO Ydi RjO hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3hHgG CKQ WeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs